2006
DOI: 10.2174/138161206776389868
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cleft Lip, Maxillary Hypoplasia, Hypoxia and Phenytoin

Abstract: Cleft lip (CL) is a common malformation that has both genetic and exogenous causes. The main pharmaceutical cause is exposure to phenytoin during early facial development in the 5th to 6th weeks of gestation. Phenytoin also causes CL if administered to pregnant rats during the period of early facial development. Evidence is presented that in the pregnant rat, a teratogenic dose of phenytoin slows the early embryonic heart and causes a prolonged period of embryonic hypoxia. It is proposed that this hypoxia, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 151 publications
0
48
0
1
Order By: Relevance
“…It has been suggested that similar effects could occur in the human and drugs with I Kr /hERG inhibition as an unwanted side effect could be potential teratogens (Karlsson et al, 2007;Nilsson et al, 2010). In this respect, phenytoin is interesting as it is a known human teratogen (Briggs et al, 2002) that induces malformations that are consistent with periods of embryonic hypoxia (Danielsson et al, 2005;Webster et al, 2006;Webster and Abela, 2007). Phenytoin inhibits potassium, sodium, and calcium channels and if the human embryonic heart is more sensitive to this combination of inhibition than the adult heart it may explain the mechanism of teratogenesis.…”
Section: Teratologymentioning
confidence: 99%
“…It has been suggested that similar effects could occur in the human and drugs with I Kr /hERG inhibition as an unwanted side effect could be potential teratogens (Karlsson et al, 2007;Nilsson et al, 2010). In this respect, phenytoin is interesting as it is a known human teratogen (Briggs et al, 2002) that induces malformations that are consistent with periods of embryonic hypoxia (Danielsson et al, 2005;Webster et al, 2006;Webster and Abela, 2007). Phenytoin inhibits potassium, sodium, and calcium channels and if the human embryonic heart is more sensitive to this combination of inhibition than the adult heart it may explain the mechanism of teratogenesis.…”
Section: Teratologymentioning
confidence: 99%
“…Danielsson et al (2003) demonstrated that teratogenic doses of these drugs induce bradycardia and hypoxia in the embryo but not in the mother. During the hypoxic period, embryos show areas of hemorrhage and/or edema in areas that subsequently develop abnormally (Webster et al, 1996(Webster et al, , 2006. Embryonal cardiac arrythmia and transient hypoxia have also been suggested as mechanisms for the teratogenicity of anticonvulsants Danielsson, 1998, 2002).…”
Section: Hypoxia and The Edema Syndrome In Mammalian Embryosmentioning
confidence: 99%
“…This is generally regarded as being hypoxic, with most normal tissues having an oxygen tension of 20-40 mm Hg (Webster, 2007). In normal mouse, rat, and quail embryos, during the organogenic period, there are many areas that stain with pimonidazole, and the location of these areas changes with the age of the embryo (Lee et al, 2001;Danielsson et al, 2003a;Webster et al, 2006;Naňka et al, 2006). The interpretation that the stained cells in the embryos are hypoxic is supported by the demonstration that pimonidazole mostly colocalizes with hypoxia inducible factor (HIF-1a) and vascular endothelial growth factor (VEGF) in mouse and quail embryos (Lee et al, 2001;Naňka et al, 2006).…”
Section: Physiological Hypoxiamentioning
confidence: 99%